2012
DOI: 10.4269/ajtmh.2012.12-0251
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Zoonotic Canine Leishmaniasis in Northeastern Brazil: Pet Attachment and Adoption of Community Leishmania Prevention

Abstract: Abstract. Visceral leishmaniasis (VL), caused by Leishmania infantum chagasi (L.i. chagasi syn. infantum) in northeastern Brazil, was responsible for 51,000 new VL cases from 1980 to 2003. Household presence of L. infantum-infected dogs is a major risk factor for human infection. Despite culling of dogs based on seropositivity, canine L. infantum seroprevalence remains near 20%, suggesting that dog culling is ineffective for preventing VL spread. We administered a cross-sectional survey to 224 households withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 36 publications
0
17
0
2
Order By: Relevance
“…Dogs with leishmaniasis have a similar pathogenesis to human VL. In addition, canine leishmaniasis is a primary target for public health interventions in multiple endemic areas, including culling, vaccination and/or therapy [5, 26]. …”
Section: Discussionmentioning
confidence: 99%
“…Dogs with leishmaniasis have a similar pathogenesis to human VL. In addition, canine leishmaniasis is a primary target for public health interventions in multiple endemic areas, including culling, vaccination and/or therapy [5, 26]. …”
Section: Discussionmentioning
confidence: 99%
“…While studies have shown that vigilant surveillance and culling can reduce the canine prevalence of VL to a degree, impacts on human infection are more difficult to ascertain (339). Limitations in diagnostic sensitivity likely lead to false-negative diagnoses for a large number of asymptomatic dogs, delays between testing and dog removal increase the likelihood of transmission, and the financial and emotional costs of the policy implemented in Brazil are high (329,339,340). The use of permethrin or deltamethrin collars or topical applications has shown efficacy in reducing sandfly feeding and transmission in areas of endemicity (341,342).…”
Section: Preventionmentioning
confidence: 99%
“…Clinical ZVL has also been associated with poor nutrition (328). Many of the same factors associated with human ZVL also apply to owner characteristics associated with risks for canine VL (271,272,329). Vertical transmission has been characterized for dogs and people, causing an increased risk for infants born to parasitemic mothers (330).…”
Section: Fig 10mentioning
confidence: 99%
“…Global canine mortality due to leishmaniosis is unknown. Data generated based on CanL seropositive dog culling in multiple countries including Brazil, suggests that canine mortality associated with CanL is 20-30 times greater than that of humans (Alvar et al, 2013; Costa et al, 2007; Esch et al, 2012; Palatnik-de-Sousa et al, 2001). Visceralizing leishmaniasis, due to its systemic presentation, is commonly termed leishmaniosis.…”
Section: Introductionmentioning
confidence: 99%